Clinicopathological characteristics of young never smoker females with oral cavity squamous cell carcinoma: A STROBE compliant retrospective observational study. Issue 5 (5th February 2021) - Kwon, Minsu; Lee, Dong Kyu; Choi, Seung-Ho; Nam, Soon Yuhl; Kim, Sang Yoon; Lee, Yoon Se
Abstract : Abstract: Although the incidence of oral cavity cancer (OCC) in young never smoker females is increasing worldwide, there has been little research on the etiologies and characteristics of these patients to date. In this study, we sought to evaluate the annual increase in OCC incidence in young never smoker females (YNSF) in our hospital as well as to investigate their clinicopathological characteristics and different disease courses compared with those of other OCC patients. We retrospectively reviewed the medical records of patients who were diagnosed and treated at our tertiary referral hospital from 2006 to 2016. The annual incidence of OCC and proportion of YNSF (never smoker females aged 45 years or younger at the time of diagnosis) among the enrolled OCC patients were evaluated. The characteristics and prognosis of the YNSF group were analyzed using their clinicopathological and survival data. Among the OCC patients primarily enrolled in this study, the proportion of YNSF did not show significant annual increase. There were 32 YNSF among 354 OCC patients (9%), who were ultimately included for the analyses of clinicopathological characteristics and survival. However, YNSF showed no significant differences compared with other OCC patients, even in subgroup analyses for overall survival. Our study did not demonstrate significant changes in the annual proportion of YNSF among OCC patients. In addition, differences in neither clinicopathological characteristics nor survival were noted between YNSF and other OCC patients.